2018
DOI: 10.1007/s00784-018-2644-2
|View full text |Cite
|
Sign up to set email alerts
|

Mineral density changes in bovine carious dentin after treatment with bioactive dental cements: a comparative micro-CT study

Abstract: Based on minimally invasive concept, materials with remineralization potential can be used to preserve diseased but still repairable dental tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Moreover, micro‐CT allows longitudinal follow‐up of the samples (Neves et al . ). This is the first study to report volumetric change values of endodontic materials after immersion in distilled water or PBS.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, micro‐CT allows longitudinal follow‐up of the samples (Neves et al . ). This is the first study to report volumetric change values of endodontic materials after immersion in distilled water or PBS.…”
Section: Discussionmentioning
confidence: 97%
“…According to this methodology, solubility and dimensional changes can be evaluated by the same experiment (Silva et al 2017). Moreover, micro-CT allows longitudinal follow-up of the samples (Neves et al 2019). This is the first study to report volumetric change values of endodontic materials after immersion in distilled water or PBS.…”
Section: Discussionmentioning
confidence: 99%
“…The glass ionomer cement (GIC) family is the most widely used selfadhesive bulk-fill material in direct restorations [3]. GICs have other interesting properties that are directly linked to their chemistry, such as moisture tolerance [4] and rechargeable fluoride release from fluoroalumino-silicate (FAS) fillers, which leads to potential dental hard tissue remineralization [5] and cariostatic effects [6]. These materials can be resin-free, such as the GICs and their improved formulation-called highviscosity glass ionomer cements (HV-GICs)-or may contain additional resinous content (mainly 2-hydroxyethylmethacrylate), such as resinmodified glass ionomer cement (RM-GIC) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Although many studies have evaluated the porosity of different types, mixing methods, and brands of GICs [ 14 16 17 27 28 ], very few have used the nondestructive micro-CT technique [ 18 19 ]. Micro-CT allows evaluation of the bulk of the entire specimen, the visualization of its internal structure, and volumetric analysis [ 30 ]. In the present study, a statistically significant difference in total porosity was observed between the 2 HVGICs, with Vitro Molar showing lower porosity results than the conventional GICs.…”
Section: Discussionmentioning
confidence: 99%